1990
DOI: 10.1002/1097-0142(19900815)66:4<722::aid-cncr2820660421>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and serologic markers of stage and prognosis in small cell lung cancer. A multivariate analysis

Abstract: The respective pretreatment prognostic impacts of the following markers were evaluated in 125 patients with small cell lung cancer (SCLC): lactic dehydrogenase (LDH), serum thymidine kinase (S-TK), carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), and tissue polypeptide antigen (TPA). More traditional clinical and serologic markers were also evaluated. Univariate analysis showed that all of the biochemical markers mentioned above, the Karnofsky index (KI) and the patient's sex were related to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…It is of considerable interest in clinical settings because its level is highly dependent on cell growth. TK1 is a sensitive and specific marker for prognosis (16,18,19), for the monitoring of the outcome of cancer therapy (25)(26)(27)(28), and for the screening of healthy individuals for the risk of malignant disease (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of considerable interest in clinical settings because its level is highly dependent on cell growth. TK1 is a sensitive and specific marker for prognosis (16,18,19), for the monitoring of the outcome of cancer therapy (25)(26)(27)(28), and for the screening of healthy individuals for the risk of malignant disease (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Thymidine kinase activity has been used as a proliferation marker since 1980 in serum and cytosol fractions of tissues. It is almost undetectable in normal serum (14)(15)(16), but increases to varying degrees in malignant tumors, depending on their type, stage (16), whether they are fast or slow growing (17), and whether they are treated or untreated (18). In a clinical study of 1,692 breast cancer patients (19), TK1 activity in the cytosol was correlated to a shorter survival time and poor outcome using endocrine treatment (tamoxifen) (20).…”
Section: Introductionmentioning
confidence: 99%
“…NSE was not included in these studies, but a close correlation between LDH and NSE has been shown (J0rgensen et al, 1988). In numerous investigations (Carney et al, 1982;Akoun et al, 1985;Cooper et al, 1987;J0rgensen et al, 1989;Gronowitz et al, 1990) a close correlation between disease extent and NSE was found. The lack of influence of NSE on probability for CR vs that of a PR may partly be caused by the extremely difficult distinction between the responses.…”
Section: This Investigation Includedmentioning
confidence: 86%
“…The concentration of NSE correlates with the extent of disease, but independent of this relationship NSE in itself contributes to the prognosis of the patients (J0rgensen et al, 1988), albeit the prognostic impact of NSE has not been significant in all investigations (Carney et al, 1982;Akoun et al, 1985;Gronowitz et al, 1990). …”
mentioning
confidence: 99%
“…pooling SCLC and NSCLC). This perturbs the interpretation of the results because it is now demonstrated that CEA level has a prognostic influence on patients with SCLC (Gronowitz et al, 1990). Moreover, only univariate analyses of survival have been done and, inasmuch as CEA is related to disease extent, its value as an independent prognostic variable is questionable.…”
Section: Discussionmentioning
confidence: 99%